ANALISA PERHITUNGAN ULANG RODAGIGI MATAHARI PADA GARDAN BELAKANG LAND ROVER - HP, Bambang; Budi Santoso, Edy; Nurtjahyono (PPM Sdirjianbang Akademi Militer, 2024)
This study aims to evaluate the need for a sun gear in the rear axle of the Land Rover, which is difficult to source domestically. The research focuses on determining the appropriate size, suitable materials, and specific details. Quantitative analysis is conducted to recalculate and obtain the required dimensions. The research concludes that the appropriate size has been determined through meticulous calculations, enabling the fabrication of a sun gear suitable for the Land Rover. This study is crucial due to the urgent need for spare parts to ensure the smooth progress of Taruna's basic driving training